2000
DOI: 10.1121/1.1329836
|View full text |Cite
|
Sign up to set email alerts
|

Relative contributions of passband and filter skirts to the intelligibility of bandpass speech: Some effects of context and amplitude

Abstract: Warren et al. (1995) reported over 90% intelligibility for everyday sentences reduced to a 1/3-octave band (center frequency 1,500 Hz, slopes 100 dB/octave, slow-rms peak levels 75 dB). To investigate the basis of this high intelligibility, Warren and Bashford (1999) partitioned the sentences. Surprisingly, the rectangular 1/3-octave passband had only 24% intelligibility, whereas the filter skirts separated by a 1/3-octave notch had an intelligibility of 83%, despite their severe spectral tilts. Experiment 1 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…This was found for filtered speech in quiet and when presented in broadband or notch-filtered noise (i.e., noise filling the spectral gaps of missing speech). These results are consistent with a long lineage of studies by Warren and colleagues demonstrating a super-additivity of sparsely represented speech (e.g., Warren et al, 1995;Warren et al, 1997;Warren and Bashford, 1999;Healy and Warren, 2003;Warren et al, 2005;Bashford et al, 2000). That is, significant speech recognition can be obtained with narrow speech bands if they sufficiently sample the frequency spectrum.…”
Section: Discussionsupporting
confidence: 90%
“…This was found for filtered speech in quiet and when presented in broadband or notch-filtered noise (i.e., noise filling the spectral gaps of missing speech). These results are consistent with a long lineage of studies by Warren and colleagues demonstrating a super-additivity of sparsely represented speech (e.g., Warren et al, 1995;Warren et al, 1997;Warren and Bashford, 1999;Healy and Warren, 2003;Warren et al, 2005;Bashford et al, 2000). That is, significant speech recognition can be obtained with narrow speech bands if they sufficiently sample the frequency spectrum.…”
Section: Discussionsupporting
confidence: 90%
“…Another study also employed the 1 / 3-octave everyday sentences centered at 1.5 kHz with transition bands of 100 dBA/octave, and truncated the filter skirts at a series of increasing distances from the cutoff frequency using 2000-order FIR filtering. It was found that statistically significant contributions from these transition bands could be made for frequencies attenuated by 30 dBA, so that the nominal 1 / 3-octave band had a much larger effective bandwidth ͑i.e., the range of frequencies contributing to intelligibility͒ that extended to almost one octave ͑Warren, Bashford, and Lenz, 2000͒. While these experiments using 2000-order FIR filtering demonstrated the major role played by transition bands in determining intelligibilities of filtered speech, none of these experiments employed filter slopes steep enough to remove all contributions from transition bands, and so permit measurement of passband intelligibilities.…”
Section: Introductionmentioning
confidence: 98%
“…Namely Bashford et al found a score of 26% for the 1/3 octave 96 dB/oct filter. After the electronic filters had been replaced with very high order digital filters, the score dropped to 4% (Bashford et al, 2000).…”
Section: Warrenmentioning
confidence: 99%